Class S: appropriation of ‘lesbian’ subculture in modern Japanese literature and New Wave cinema - Shamoon, Deborah (Cultural Studies, 2021)
In the 1920s in Japan, girls attending single-sex secondary schools developed a girls’ culture (shōjo bunka) or subculture to insulate themselves temporarily from the pressures of patriarchal society. Part of this subculture was a practice called s kankei (s or sister relationships), also called Class S, which were same-sex romantic attachments between classmates, condoned at the time as a temporary practice relationship that would end upon graduation, followed by an arranged marriage. Although s relationships were not ‘lesbian’ in the contemporary sense, literature and film created by men in the 1920s through the 1960s appropriated aspects of girls’ culture, including exploitative representation of female homosexuality. One example is Manji (Quicksand, 1928) by Tanizaki Jun’ichirō, which depicts an s relationship as lurid and perverse. Kawabata Yasunari plagiarized from his female disciple Nakazato Tsuneko in order to publish the most popular Class S novel of the era, Otome no minato (Harbor of Girls, 1937). Kawabata also included exploitative scenes of female homosexuality in his novel Utsukushisa to kanashimi to (Beauty and Sadness, 1963). Both Tanizaki’s and Kawabata’s novels were made into films by New Wave directors, Manji in 1964 by Masumura Yasuzō and Beauty and Sadness in 1965 by Shinoda Masahiro, and featured the first depictions of ‘lesbianism’ in Japanese film. Although these films reinscribe the male gaze, they helped inspire a nascent gay culture and opened the way for more authentic gay cinema. This essay recenters girls’ culture in modern Japanese literature and film, and discusses the variable meaning of female homosexuality for different audiences.
Keywords: approches et analyses; arts; asie; discipline; discours dominant; japon; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; systèmes d'oppressions; études culturelles; études littéraires

Hindu nation and its queers: Caste, islamophobia, and de/coloniality in India - Upadhyay, Nishant (Interventions: international journal of postcolonial studies, 2020)
Le jugement de la Cour suprême indienne de 2018 dépénalisant l'homosexualité a été qualifié d'"acte décolonial". Article 377, qui criminalisait l'homosexualité, était une loi coloniale introduite par les Britanniques en Inde, que l'État postcolonial a maintenue jusqu'en 2018. Le jugement peut être « décolonial » dans son intention, mais il y a d'autres processus simultanés en jeu qui ne sont pas si décoloniaux dans la pratique ; cet essai soutient que ces processus sont le colonialisme, la suprématie brahmanique et l'islamophobie. La violence basée sur la caste fait partie intégrante de l'hindouisme et est étroitement liée à d'autres matrices d'oppression, faisant de la caste le fondement de toute revendication de l'hindouisme en tant que queer, trans et non conforme au genre amical. Étudiant les récentes réponses nationalistes hindoues en faveur de la dépénalisation de l'homosexualité en Inde, cet essai retrace comment la droite hindoue déploie la queerness pour propager ses agendas islamophobes, castistes et homohindunationalistes. L'essai défend la décolonisation du droit, de l'État.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cours; discours dominant; fem3400; inde; islamophobie; premier cycle; périodes historiques; queer; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Pour une théorie générale de l'exploitation. Deuxième partie: repartir du bon pied - Delphy, Christine (Mouvements, 2004)
https://www-cairn-info.proxy.bibliotheques.uqam.ca/revue-mouvements-2004-1-page-97.htm
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; cours; cycles supérieurs; discipline; discours dominant; exploitation; fem9000; intersectionnalité; marxisme; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; thématiques; travail; violences; économie; économie sociale

Doing fieldwork on women in theocratic Islamic states: A critique of the politics of empiricism - Mojab, Shahrzad (Resources for Feminist Research, 2001)
This paper examines the way some feminist advocates of cultural relativism adopt positivism and empiricism in order to discredit the radical critique of Islamization of gender relations in Iran. It argues that relativists use the positivist/empiricist cult of experience and objectivity in order to undermine the critique of policies and practices that oppress the women of Iran. The choice of a method of inquiry is not based on methodological considerations only. The researcher's political preferences, implicit or explicit, plays a significant role in the entire research process, especially in the study of sensitive issues. Although one may identify a methodological tradition with a certain brand of politics, the paper argues that methodological paradigms enter into changing relationships with structures of power.
Keywords: approches et analyses; asie; cours; discipline; discours dominant; fem1000; iran; méthodologie; premier cycle; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; épistémologie

Contraception masculine et querelles de genre - Oudshoorn, Nelly; Akrich, Madeleine; Le Doaré, Hélène (Cahiers du Genre, 1999)
Depuis la seconde guerre mondiale, treize nouveaux contraceptifs féminins ont été émis au point alors que les contraceptifs masculins sont à peu près inchangés depuis quatre cents ans. La responsabilité contraceptive, avec les risques qui en découlent pour la santé, est donc attribuée principalement aux femmes. Cet article se propose d’analyser le rôle de différents acteurs dans la réécriture éventuelle des rapports de genre autour de la contraception. Nous nous concentrerons sur le cas des nouvelles techniques contraceptives, surtout masculines, et la manière dont leurs utilisateurs sont définis. Alors que la plupart des travaux en sociologie des techniques insistent sur le rôle de l’innovation dans cette définition de l’utilisateur, nous montrerons qu’aux côtés des scientifiques, les féministes et les journalistes ont joué un rôle important dans la configuration des utilisateurs potentiels de ces techniques contraceptives : ils ont construit une grande variété de représentations de la masculinité et des utilisateurs hommes. Ces représentations sont utilisées soit pour montrer qu’il n’y a pas d’obstacle culturel à l’acceptabilité de ces techniques, soit à l’inverse, pour en dénoncer le caractère utopique.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; asie; cours; discipline; discours dominant; europe; hétérosexisme; inégalités; justice reproductive; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques